The use of novel Therakos™ Cellex® for extracorporeal photopheresis in treatment of graft‐versus‐host disease in paediatric patients. (21st August 2013) - Rangarajan, Hemalatha G.; Punzalan, Rowena C.; Camitta, Bruce M.; Talano, Julie‐An M.
Summary Extracorporeal photopheresis (ECP) is an established second line treatment option for graft‐versus‐host disease (GVHD) post‐haematopoietic progenitor cell transplant. At our centre, the Therakos™ Cellex® has replaced the Therakos™ UVAR‐XTS™ machine for ECP since 2009. We reviewed the records of 385 procedures using the Therakos™ Cellex® for safety and tolerability. Nine patients underwent ECP for GVHD. The median age was 13·5 years (range 3·7–24) and weight was 49·2 kg (range 18·5–86·3). The mean duration per procedure was 106 min (range 60–205). Fifteen (3·9%) procedures were cancelled and 10 (2·6%) were delayed, with central venous line (CVL) issues being the most frequent problem. With the use of prophylactic tissue plasminogen activator, fewer CVL‐related occlusions were observed (4·7% vs. 2·3%). There was one episode of a CVL‐associated thrombosis and one episode of delayed bleeding. There were four episodes of viral reactivation, four CVL‐associated infections (1142 catheter days) and one episode of systemic inflammatory response syndrome. No patient experienced symptomatic hypotension. This is the first report outlining the safety and tolerability of the Therakos™ Cellex® device for ECP in children and young adults.